Application of generalized multiplicative reliability function to Lithuanian’s survival data - Senkuvienė, Rasa (Lietuvos matematikos rinkinys, 2000)
Generalized multiplicative survival function was fitted to Lithuanian 1980–1996 years mortality data in 40+ age group. Quality of fit was evaluated using non-parametric variance estimation.